(untitled) (Research, Society and Development, 2023)
The overwhelming growth of cities and the migration of citizens from the countryside to urban centers in search of better living conditions triggered a crisis in the management of cities. In addition to issues related to food, work and human rights of Brazilians, there is still a land issue to be resolved by national authorities. It was for this reason that in 2017, as a result of the rules arising from the Code of Civil Procedure (2015), Law No. requirements contained in the City Statute (2001), which had its content changed in search of better efficiency of urban public housing policies. With this, there was the improvement of the institute of urban adverse possession on a collective basis, given that it became more effective in situations of housing irregularity. The main objective of this work is to analyze how the Federal Law 13.465/2017 was applied to cases of adverse possession in Brazil. The research is characterized by the deductive method of research, seeking the largest number of studies on the subject, in order to correlate them with the bibliographic material available in laws, published articles, legal doctrines and jurisprudential understandings. Thus, this article presents the trajectory of the urban collective adverse possession institute from general conceptions about the institute, to specifically specify the contributions to the legal system, as well as the organization of legal reflection in relation to actions on the issue in the national context.